Systematic Literature Review Of Social Sustainability Approach In Palm Oil Industry - Maisarahmokti, Amir Hamzah Sharaai (International Journal of Advanced Science and Technology, 2020)
Sustainability had become an issues which discussed widely in various field nowdays. By using systematic literature review to obtain materials, the ‘social sustainability’ issues we bring in this paper specifically focusing in palm oil industrial area as this industry’s demand is increasingly worldwide- with Malaysia rank the second as reported by Workman D. in World’s Top Export. Despite that, agriculture sector were reported as one of the major pollutant for water pollution in Malaysia which thus create a great focus to discuss. Few existing indicators used in this industry were included; Roundtable on Sustainable Palm Oil (RSPO), Social Life Cycle Assessment (S-LCA), Palm Oil Sustainability Assessment (POSA) and also Social Sustainability Index (SSINDEX). Some of the highlighted issues concluded were the effectiveness of each approach to be adapt as the main method in assessing social sustainability in palm oil industry.